Fungos endofíticos: prospecção de atividade biocatalítica e aplicação biotecnológica - Lisboa, Helen Cristina Fávero [UNESP] (2015)
The endophytic fungi are microorganisms that live in the intercellular spaces of plants and are known for their potential for the production of important products of biotechnological interest, such as enzymes. These have been widely used in industry because they catalyze reactions with greater specificity than conventional forms of chemical reactions, thereby making the endophytic fungus a promising alternative to produce these biocatalysts. Thus, this study aimed to prospect for enzymes of biotechnological interest as lipase, esterase, epoxide hydrolase, nitrilase, acylase, amidase and protease in endophytic fungi and evaluate their biotechnological applications, focusing on the use of the crude extract containing lipase in the transesterification process and bioremediation. Seventy five endophytic fungi were submitted to prospecting biocatalytic activity, where 66 showed lipase / esterase activity, 16 epoxide hydrolase, 24 acylases, 50 proteases, 10 nitrilase and 64 amidase. Fungi with satisfactory biocatalytic activity against different methodologies and substrates were found, showing the versatility of endophytes in the production of enzymes. The fungi Mycosphaerella coacervata was selected to evaluate the activity and partial characterization of extracellular lipase crude extract. The microorganism showed maximum enzyme production when grown for 48 hours at 28°C (486 U / L), and remained stable up to 6 months stored at -2°C. The crude extract containing the enzyme showed maximum activity at 37°C at pH 8.0. The thermal stability was observed in the range of 30 to 60°C (residual activity above 80%) and its stability at the pH between 6.0 and 9.0 (residual activity exceeding 80%). The enzyme was stable (residual activity above 90%) in the presence of acetone, methanol, ethanol, isopropanol and hexane at concentrations of 20 and 50%. Good stability was observed also in relation to different...